BIODEGRADATION OF SYNTHETIC TEXTILE DYES BY CHITOSAN BEADS CROSS-LINKED LACCASE FROM Pleurotus ostreatus IBL-02 - F. Jamil; M. Asgher; F. Hussain; H. N. Bhatti (Journal of Animal and Plant Sciences, 2018)
Laccase (EC.1.10.3.2) a blue copper protein is remarkable, ecologically well disposed and productive biocatalyst that can degrade the toxic contaminants. The utilization of laccase for the detoxification of toxic pollutants is extensively restricted by its vulnerability to changes in operational conditions and its poor reusability. To overcome this problem, indigenously produced laccase from Pleurotus ostreatus IBL-02 was immobilized using glutaraldehyde as cross-linker. Maximum immobilization efficiency (76.2%) was noticed with 3% Chitosan, cross-linked by 3% solution of glutaraldehyde. Cross-linking significantly altered the kinetic parameters Km and Vmax of laccase. The affinity of substrate towards biocatalyst improved (Km decreased) consequently upgraded catalytic activity (increased Vmax). Immobilization significantly raised the temperature optima while shifted the optimum pH towards slightly neutral from acidic. The presence of laccase in immobilized beads was also confirmed by Energy Dispersive X-ray (EDX) analysis. Immobilized laccase was used to decolorize five different synthetic textile dyes. Chitosan cross-linked laccase decolorized all the dyes more efficiently as compared to control.
Keywords: Laccase; Chittosan; Cross-linking; Immobilization; Biodegradation